The other side of Zen a social history of Sōtō Zen Buddhism in Tokugawa Japan - Williams, Duncan Ryūken 1969- (Princeton, NJ Princeton University Press, 2021)
Frontmatter -- CONTENTS -- LIST OF FIGURES AND TABLES -- ACKNOWLEDGMENTS -- NOTES ON TRANSLITERATION AND ABBREVIATIONS -- ONE Toward a Social History of Sôtô Zen -- TWO Registering the Family, Memorializing the Ancestors: The Zen Temple and the Parishioner Household -- THREE Funerary Zen: Managing the Dead in the World Beyond -- FOUR The Cult of Dôryô Daigongen: Daiyûzan and Sôtô Zen Prayer Temples -- FIVE Medicine and Faith Healing in the Sôtô Zen Tradition -- CONCLUSION The Other Side of Zen -- APPENDIX A: NYONIN JÔBUTSU KETSUBONKYÔ ENGI (THE ORIGINS OF THE BLOOD POOL HELL SUTRA FOR WOMEN'S SALVATION) -- APPENDIX B: SHINSEN GEDOKU MANBYÔEN FUKUYÔ NO KOTO (HOW TO PREPARE AND TAKE THE WIZARD MOUNTAIN "POISON-DISPELLING" PILL THAT CURES ALL ILLNESSES) -- NOTES -- GLOSSARY OF CHINESE AND JAPANESE -- BIBLIOGRAPHY -- INDEX
Popular understanding of Zen Buddhism typically involves a stereotyped image of isolated individuals in meditation, contemplating nothingness. This book presents the "other side of Zen," by examining the movement's explosive growth during the Tokugawa period (1600-1867) in Japan and by shedding light on the broader Japanese religious landscape during the era. Using newly-discovered manuscripts, Duncan Ryuken Williams argues that the success of Soto Zen was due neither to what is most often associated with the sect, Zen meditation, nor to the teachings of its medieval founder Dogen, but rather to the social benefits it conveyed.Zen Buddhism promised followers many tangible and attractive rewards, including the bestowal of such perquisites as healing, rain-making, and fire protection, as well as "funerary Zen" rites that assured salvation in the next world. Zen temples also provided for the orderly registration of the entire Japanese populace, as ordered by the Tokugawa government, which led to stable parish membership.Williams investigates both the sect's distinctive religious and ritual practices and its nonsectarian participation in broader currents of Japanese life. While much previous work on the subject has consisted of passages on great medieval Zen masters and their thoughts strung together and then published as "the history of Zen," Williams' work is based on care ul examination of archival sources including temple logbooks, prayer and funerary manuals, death registries, miracle tales of popular Buddhist deities, secret initiation papers, villagers' diaries, and fund-raising donor lists
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Keywords: RELIGION / Buddhism / Zen (see also PHILOSOPHY / Zen); Religion; Princeton University Press; Zen master; Monasticism; Writing; Sect; Rite; PHILOSOPHY / Zen; Kokugakuin University; Monastery; Leprosy; Memorial service (Orthodox); Nichiren; religion in Japan; Sanskrit; Monumenta Nipponica; Transliteration; Posthumous name; University of Hawaii Press; HISTORY / Asia / Japan; Akadama Jinkyōgan; Akutsu Shōemon; Amida Buddha; Aruga Kizaemon; Birnbaum, Raoul; Buddhahood; Butsujō; Chōjuin Temple; Daiyūgan; Daranisuke; Dharma succession; Dōryō Daigongen; Enjōji Temple; Funrei; Gedokuen; Gokūshiki; Hakone Betsuin; Hatano Yoshishige; Hirose Ryōkō; Ichimantai Jizō; Ishikawa Rikizan; Izumiya Sakuemon; Jippensha Ikku; Jōdo Shin sect; Kakumon; Kangakuya pharmacy; Kurozumikyō; LaFleur, William; Lalou, Marcelle; Dharma name; Buddhist studies; Christian; Christianity; Constipation; Abbreviation; Early modern period; Faith healing; Fumi-e; Ginger